DYSONTOGENESIS AND REDUCTION OF CHILDREN'S GAME: ANALYSIS, CONSEQUENCES, WAYS TO SOLVE PROBLEMS - Kruty, Kateryna; Holiuk, Oksana; Rodiuk, Nataliia; Bilska, Olha; Desnova, Iryna; Pakhalchuk, Natalia; Blashkova, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The research focuses on the philosophical aspects of children's play. The aim of the study is to analyze modern approaches to the classification and development of preschoolers` play activities, the negative phenomena of dysontogenesis and reduction of play. The authors analyzed the results of a survey of undergraduate students in specialty Preschool Education and their relatives about children's memories of the play, game situations and the impact of play competence (or lack of it) on adult life.Basic research methods are interview, surveys, statistical analysis.The main results of the study give grounds to claim that play is not the only leading activity of a senior preschooler. Even accepting the concept of "leading" and "non-leading" activities, it turns out that children's experimentation during preschool takes no less "leading" position than play. This fact radically changes the perception of conditions, goals and values in the organization of children's lives.The author's team proved that the dysontogenesis of play and non-acceptance of children's experimentation in preschool age leads to further distortion of the trajectory of development. The author's interpretation of the terms "play reduction", "play dysontogenesis", "amplification" and "simplification" of children's play is proposed.